The psychology of goals - Moskowitz, Gordon B.; Halvorson, Heidi Grant-, 1973- (Guilford Press, 2009)
Bringing together leading authorities, this tightly edited volume reviews the breadth of current knowledge about goals and their key role in human behavior. Presented are cutting-edge theories and findings that shed light on the ways people select and prioritize goals; how they are pursued; factors that lead to success or failure in achieving particular aims; and consequences for individual functioning and well-being. Thorough attention is given to both conscious and nonconscious processes. The biological, cognitive, affective, and social underpinnings of goals are explored, as is their relati.